دراسة ظاهرة دوران السفينة على المزلق المائل خلال المرحلة الأولى من الإنزال العرضي(الجانبي) - ميشيل بربهان (Latakia University Journal -Engineering Sciences Series, 2019)
تُعتبر دراسة وتحليل سلوك السفينة في أثناء إنزالها عرضياً من على مزلق مائل نحو الماء من المسائل ذات الأهمية الخاصة، نظراً لارتباط ذلك باحتمال نشوء بعض الحالات الخطرة كظاهرة دوران السفينة على المزلق المائل خلال المرحلة الأولى للإنزال العرضي. هذه الظاهرة قد تسبب انفصال المزالج عن سكك الإنزال وتهشمها، وبالتالي حدوث تدمير لمنشأة الإنزال الانزلاقي العرضي وإلحاق الضرر ببدن السفينة. يتضمن هذا البحث شرحاً للنموذج الرياضي المقترح والخاص بدراسة السلوك الديناميكي للسفينة خلال المرحلة الأولى من مراحل الإنزال العرضي، بغية حساب عزم مزدوجة الدوران وبالتالي حساب زاوية دورانها. تمَّ إعداد برنامج حاسوبي بلغة (Visual Basic) لتنفيذ الحسابات وفقاً للنموذج المقترح. سمح ذلك بدراسة تأثير البارامترات الأساسية لمنشأة الإنزال الانزلاقي على زاوية دوران السفينة في أثناء حركتها على المزلق. Analyzing ship behaviour during lateral launching on a slant slipway towards water is considered of paramount importance due to causing some dangerous cases as the phenomenon of ship rotation on a slant slipway during the first stage of lateral launching. This phenomenon may trigger a separation of the sliding ways from the launching ways; this leads to the structure of lateral launching being destroyed, and the ship hull being damage. This study explains the mathematical model suggested for studying the dynamic behaviour of the ship during the first stage of lateral launching in order to calculate the momentum and angle of the rotation cycle. A computer program is designed to make these calculations in accordance with the suggested model. This allows studying the impact of basic parameters of the structure of lateral launching on the angle of ship rotation during its movement on the slipway.